THE EFFECTIVENESS OF STUDENT WORKSHEET TO TRAIN SCIENCE PROCESS SKILLS - Elok Sudibyo; Alimatun Fadhilatuts Naini; Wahyu Budi Sabtiawan (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2019)
This study aims to describe the effectiveness of Student Worksheets used to train science process skills. The subjects of the study were the VII grade students of the Sepuluh Nopember Middle School, Sidoarjo. The research instrument used was a student activity observation sheet and a science process skill test item. The results showed that the worksheets given were effectively used to train science process skills.